THE INFLUENCE OF INITIAL STATIC SHEAR STRESS ON POST-CYCLIC DEGRADATION OF NON-PLASTIC SILT - B.- W. Song (International Association of Lowland Technology, 2003)
Using a sequential procedure of cyclic and post-cyclic direct simple shear (DSS) tests, the strength and stiffness degradation characteristics of non-plastic silt were studied during and immediately after cyclic loading. The postcyclic degradations of strength and stiffness were considered with special reference to the effects of initial static shear stress (ISSS). The findings obtained from sequential DSS testing on non-plastic silt are: (1) strength and stiffness degradation characteristics of non-plastic silt during post-cyclic loading depend on the increase of the normalized pore pressures generated during cyclic loading, which is more marked with increasing ISSS; (2) degradation of stiffness is particularly to ISSS; (3) post-cyclic degradation relations of strength and stiffness for non-plastic silt formulated against cyclic-induced excess pore pressure should include the influence of ISSS. The methods formulated for predicting post-cyclic strength and stiffness take the effect of ISSS into consideration.